A Longitudinal Approach to Management Turnover in Small and Medium Sized Enterprises in Italy - Maria Garbelli (European Scientific Journal, ESJ, 2019)
Italian small and medium-sized enterprises have experienced their first generational turnover in the 1970s, when the founders have been succeeded by their heirs. Today, the theme does not seem to be exhausted, as much in literature, which strongly affirms the multidimensionality and criticality of the transition phase, as in the entrepreneurial reality. Part of a more comprehensive research project on management turnover, this study focuses on a specific territory, the province of Brescia, chosen for its strong industrial vocation and considered as representative of the industrial landscape of Italy. The study focuses on the small and medium-sized industrial fabric management, sampled in 524 enterprises that met the research requirements, home for a total of 2640 roles. Management data has been profiled by age, gender, position and company size. The details of the sample confirm the relevance of turnover issues to Italian SMEs. Managers longevity is higher for chairman and higher executives than other roles; furthermore, most of the examined people perform multiple roles at the same time. The longitudinal approach reveals people over 70 years old hold an average of 2 positions per person, with a strong correlation between the three most prevalent management roles analyzed. This research was supported by the SME Industrial Association of Brescia.